The Relationship Between School Climate and Compensation with Job Satisfaction of ASN Teachers in Junior High Schools Throughout Jepara Regency - Nikmah, Alfia Ainun; Azmi, M. Nawalul; Qadam , Izah Ulya (The Future of Education Journal, 2024)
This study aims to determine the relationship between school climate and teacher job satisfaction, the relationship between compensation and job satisfaction, and the relationship between school climate and compensation and ASN job satisfaction at SMPN throughout Jepara Regency. The research method applies quantitative descriptive-correlational with a quantitative approach through questionnaire studies as a data collection tool. The location of this research was at SMPN throughout Jepara Regency with a sample of 60 teachers as research respondents. This study aims to describe the level of school climate, level of compensation, level of teacher job satisfaction, the relationship between school climate and teacher job satisfaction, the relationship between compensation and job satisfaction of junior high school teachers in Jepara. This study uses a quantitative approach with a descriptive-correlational quantitative research type. The results of the study indicate that the level of school climate is in the fairly conducive category, the level of compensation is in the high category, the level of performance is in the high category, there is a relationship between school climate and teacher job satisfaction at SMPN throughout Jepara Regency, there is a relationship between compensation and teacher job satisfaction at SMPN throughout Jepara Regency, and there is a relationship between school climate and compensation and job satisfaction of SMPN teachers throughout Jepara Regency. The effective contribution of school climate to teacher job satisfaction is 5.86 percent and compensation to job satisfaction is 35.79 percent. The rest is other variables of 58.30 percent in influencing performance. The relative contribution of school climate to job satisfaction is 14 percent and compensation to job satisfaction is 86 percent.